First, bring everything to one side of the equation:
3x^2=-9x
3x^2color(blue)+color(blue)(9x)=-9xcolor(blue)+color(blue)(9x)
3x^2color(blue)+color(blue)(9x)=color(red)cancelcolor(black)(color(black)-9xcolor(blue)+color(blue)(9x))
3x^2+9x=0
Now, divide by the common factor 3:
color(blue)(color(black)(3x^2+9x)/3)=color(blue)(color(black)0/3)
color(blue)(color(black)(color(red)cancelcolor(black)3x^2+color(red)cancelcolor(black)9^3x)/color(red)cancelcolor(blue)3)=color(blue)(color(black)0/3)
x^2+3x=color(blue)(color(black)0/3)
x^2+3x=0
Now, use the distributive property backward to factor out the x term:
color(red)x*color(blue)x+color(red)x*color(blue)3=0
(color(red)x)(color(blue)(x+3))=0
Now, set each factor equal to 0 and solve for x in each one:
color(white){color(black)(
(color(red)x=0,qquadcolor(blue)(x+3)=0),
(,qquadcolor(blue)x=-3):}
These are the two solutions: x=0 and x=-3. Hope this helped!